Managerial Entrenchment and Firm Value: A Dynamic Perspective - Chang, Xin (2015)
We examine the impact of managerial entrenchment on firm value using a dynamic model with firm fixed effects. To estimate the model, we employ the long-difference technique, which is shown by our simulation to deliver the least biased estimates. Based on a large sample of U.S. companies, we document a significantly negative and causal effect of managerial entrenchment on firm value after taking into account omitted variables, reverse causality, and highly persistent endogenous variables. Additional analysis suggests that the causality running from managerial entrenchment to firm value is more pronounced than that for reverse causality.